The Role of Caucus Feto Iha Politika in Increasing Women’s Representation in Timor-Leste’s Parliament - Hidayahtulloh, Muhammad Ammar (Sospol : Jurnal Sosial Politik, 2019)
Woman had been neglected from the political affairs in the early of post-independent era. It raised the concerns of women activists on political participation. They realized Timorese women had played a significant role in fighting for independence along with male veterans. Caucus Feto Iha Politika appears as the prominent NGO in Timor-Leste that promoting gender equality in politics. It resulted the rising of women?s representation in Timor-Leste Parliament significantly. Moreover, its woman participation in parliament achieves the highest percentage in the Asia Pacific. This research lies on the question of how does the role of Caucus Feto Iha Politika in increasing women?s representation in parliament of Timor-Leste. The data obtained from primary and secondary sources by conducting the in-depth interview and library research. In order to answer the research question, the authors reiterated the three main components of NGOs roles ?implementer, catalyst, and partner by Lewis as the analytical framework. The authors humbly concluded that for increasing the number of women MPs, Caucus Feto Iha Politika played two prominent roles, as follows: 1) catalyst, by advocating the policy change of women-friendly legislative quota policy to the Government of Timor-Leste, and 2) partner, by working closely with the related stakeholders to increase the capacity of potential female candidates and elected women MPs through capacity building.